An evaluation of multi-stakeholder platforms for scaling land restoration practices in Kilolo and Lushoto districts, Tanzania - Mwihomeke, Micfanaka; Mwongera, Caroline (Bioversity International and the International Center for Tropical Agriculture, 2021)
This report investigates the functioning and outcomes of the multi-stakeholder platforms established in Tanzania. The study focused on two platforms in Kilolo and Lushoto districts and analyzed their activities to support scaling agricultural innovations. The findings show that the platforms are successful in network building and knowledge dissemination. However, there is a low participation of women and young people. In Lushoto district, the platform activities to support land restoration focused on erosion control engaging village ambassadors to disseminate knowledge on creation of water canals, afforestation, dissemination of tree seedlings to farmers and the drafting of a bylaw to protect the natural resources used as indicators in indigenous forecasting by elders. The platform in Kilolo focused on bee keeping to incentive protection of natural resources, protection of riparian zones and water bodies, terracing, dissemination of seasonal forecasts and agro-advisories, and set up farmer field schools on conservation agriculture and good agricultural practices.